2021
DOI: 10.3390/cancers13040741
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Motors: Novel Regulators and Therapeutic Targets in Colorectal Cancer

Abstract: Colorectal cancer (CRC) remains the third most common cause of cancer and the second most common cause of cancer deaths worldwide. Clinicians are largely faced with advanced and metastatic disease for which few interventions are available. One poorly understood aspect of CRC involves altered organization of the actin cytoskeleton, especially at the metastatic stage of the disease. Myosin motors are crucial regulators of actin cytoskeletal architecture and remodeling. They act as mechanosensors of the tumor env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 192 publications
(353 reference statements)
3
13
0
Order By: Relevance
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells 27,29 , but promoted migration of osteosarcoma and melanoma cells 30,67 . This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 52,68 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Depletion of this chaperone was shown to inhibit motility of breast and ovarian cancer cells 27,29 , but promoted migration of osteosarcoma and melanoma cells 30,67 . This resembles the reported opposite effects of NM-II inhibition on cell migration under different experimental conditions 52,68 and may reflect complex regulatory effects of UNC-45A-driven myofilament assembly in motile cells. We observed that loss of UNC-45A inhibited both collective migration of IEC sheets and individual cell passage through membrane pores (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Cells have other modes of migration that are unique to 3D culture such as bleb-based amoeboid migration which typically does not require protrusions 44 , 45 . Actomyosin regulation in 3D has been extensively studied in other cancer types, such as breast and colorectal cancer 17 , 44 , 46 . In the context of liver cancer, while some chemical inhibitors may be able to stop invasive phenotypes on 2D surfaces, they may not be effective in stopping 3D migration.…”
Section: Discussionmentioning
confidence: 99%
“…NMMII and PM-smACSK could be a signaling hub linking execution of cell proliferation, migration and apoptosis to signaling pathways controlling activities of ion channels and transporters. NMMII isoforms appear to regulate the metastatic potential of cancer cells and, thus, to be novel therapeutic targets [ 150 , 151 , 152 ]. Our hypothesis on NMMII as a key player in cell volume sensing broadens the spectrum of effects of NMMII in cancer cells.…”
Section: Discussionmentioning
confidence: 99%